Geographic and citizen education: conceptualization, relationship, and implementation. - Vargas Hernández, Annie (2015)
This is a bibliographical research that intents to analyze the different concepts towards the disciplines of geographic education and education for citizenship, based on comparisons among the different conceptions, and looking for the relation between them. The objective is to clarify the under study of geographic education and education for citizenship, y find the focal point, as well as the implementation of the teaching process.